Assessment of circulating free DNA as a non-invasive biomarker for diffuse large B-cell lymphoma in Egyptian patients - Wessal Elbordiny; Akram Abdel Moneim Deghady; Amr Abdel Aziz Elsayed; Ahmed Abdelrahman Shehata; Nermeen Ahmed Mohamed Eldabah (Alexandria Journal of Medicine)
Objective Diffuse large B-cell lymphoma (DLBCL) is an aggressive type of lymphoma. Circulating cell-free DNA (cfDNA) is the promising liquid biopsy in malignancy.Method Assessment of cfDNA concentration and DNA integrity index (DII) in 30 newly diagnosed DLBCL patients and correlating them with the international prognostic index.Results Circulating cfDNA concentration was significantly higher in newly diagnosed DLBCL patients than controls, while DII was significantly lower. There was a significant correlation between cfDNA concentration and adverse prognostic factors.Conclusion cfDNA concentration is potentially strong diagnostic and prognostic marker of DLBCL, however DII is only useful as a diagnostic biomarker.